2017
DOI: 10.18280/ijht.350306
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of stand-alone solar dish Stirling system for electricity generation

Abstract: This article investigates the performance of standalone solar Stirling dish system used to electrify rural houses. The yearly performance which depends on location is simulated using software developed by The National Renewable Energy Laboratory's SAM (Solar Advisor Model). Direct normal insolation, ambient temperature, density of air (altitude), sun elevation angle, and the wind speed are included in the simulation model. The model analyzes the performance of the parabolic mirror, receiver, Stirling engine, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 18 publications
(18 reference statements)
0
14
0
1
Order By: Relevance
“…It is observed that the designed PSDS system for Jamshoro has good solar potential with a net system efficiency of 23.39% and LCOE of 0.13 $/kWh. Bataineh and Taamneh 23 reported the minimum value of LCOE (0.115 $/kWh). The low value of LCOE is that the Maan city of Jordan has a high value of direct solar irradiance (2700 kWh/m 2 /y).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is observed that the designed PSDS system for Jamshoro has good solar potential with a net system efficiency of 23.39% and LCOE of 0.13 $/kWh. Bataineh and Taamneh 23 reported the minimum value of LCOE (0.115 $/kWh). The low value of LCOE is that the Maan city of Jordan has a high value of direct solar irradiance (2700 kWh/m 2 /y).…”
Section: Resultsmentioning
confidence: 98%
“…The results showed that the yearly average electrical power production was enhanced due to the technical and economic parameters and obtained the value of 12.68 GWh. Bataineh and Taamneh 23 used the SAM software, developed at National Renewable Energy Laboratory (NREL), 24 to model techno‐economic aspects for easy decision‐making in an area of renewable energy. The simulation was carried out for the solar dish system to electrify the isolated villages in Maan, Jordan.…”
Section: Introductionmentioning
confidence: 99%
“…The power block is in the shape of the cavity receiver pivoted at focal point of concentrator and consists of the Stirling engine and the generator as shown in Figure 25 99 . A typical CSP‐DSS may consists of at least one parabolic dish for small standalone application or no of parallel dishes for large capacity system 100 …”
Section: Design Development and Performance Evaluation Of Csp‐dssmentioning
confidence: 99%
“…It can operate as an engine or as a cooler by reversing the thermodynamic cycle. Since 1816, several developments led to applications in various fields such as solar converters of combined heat and power [4][5][6] for example. Whereas numerous works deal with Stirling engines at a macroscopic scale [7], only a few works concern miniaturized Stirling engines.…”
Section: Introductionmentioning
confidence: 99%